Short Communication: Habitat and population characteristics of the endemic Java Tree Frog (Rhacophorus margaritifer) in Ranca Upas, West Java, Indonesia - TINA SAFARIA NILAWATI; HERNAWATI HERNAWATI; REZA AHMAD TAUFIK (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Nilawati TS, Hernawati, Taufik RA. 2019. Short Communication: Habitat and population characteristics of the endemic Java Tree Frog (Rhacophorus margaritifer) in Ranca Upas, West Java, Indonesia. Biodiversitas 20: 1644-1649. The Java tree frog (Rhacophorus margaritifer) is one of the endemic frogs of Indonesia. Ranca Upas forest, West Java, Indonesia is one of the habitats of this species which is threatened by the extension of the ??campground and tourism area. The aim of this study was to identify the habitat and population characteristics of Rhacophorus margaritifer in Ranca Upas forest. Data was collected through Capture-Mark-Release-Recapture method in every 100 m distance of a 300 m transect, along the river. The captured frogs were tagged using modified shoelaces. Habitat characteristics were analyzed descriptively and quantitatively, population number was estimated by the Schnabel method, and population distribution was calculated using the Morisita distribution index. The results showed that R. margaritifer habitat was at an altitude of 1630-1670 m asl with 16.6 oC average air temperature and 90.8% air humidity. The habitat was near river with clear water and mud substrate at 14.8 oC water temperature, 0.068 m/s water velocity, and neutral acidity. Furthermore, three species of plants, namely Strobilanthes crispus, Curculigo capitulata, and Cyathea sp. were identified to be very often used by R. margaritifer. Population abundance of R. margaritifer was estimated to be 286 individuals, with 5 individuals /100m2 density and it showed a clumped disp.ersion. Average size of frogs found in the study area was 40 mm Snout to Vent Length (SVL) and the range was 36 to 65 mm. This showed that the location is dominated by young frogs and the study area is a good habitat for R. margaritifer.